Detection of Brains Tumors in MRI Images by using MATLAB - S.Roselee, NorShafiqah; Wan Mahmud, Wan Mahani Hafizah (Evolution in Electrical and Electronic Engineering, 2023)
Detecting brain tumors is a critical task in the medical industry, and magnetic resonance imaging (MRI) is frequently used to find them. However, detecting early-stage brain tumors in MRI images can be challenging due to the size and location of the malignant tissue. This work suggests utilizing MATLAB to apply image processing methods including the median filter, segmentation, feature extraction, and classification to this problem. In the suggested method, images are preprocessed using the median filter, features are extracted using the gray level co-occurrence matrix (GLCM), and the results are then classified using a Support Vector Machine (SVM). As part of the work, a Graphical User Interface (GUI) will be developed for the identification and classify of brain tumors using MRI images. The MATLAB created GUI can be used to identify disorders and support the early expose and management of brain tumors. Through the use of image preprocessing techniques and classify models, high accuracy in the identification and categorization of brain tumors has been attained.